The first report of a vauxiid sponge from the Cambrian Chengjiang Biota. (January 2020) - Luo, Cui; Zhao, Fangchen; Zeng, Han
Abstract: Non-spicular sponges constitute >8% of the extant sponge biodiversity at the species level, yet their evolutionary history is poorly known due to a sparse fossil record. The genus Vauxia, previously only known from middle Cambrian (Miaolingian, Wuliuan) Lagerstätten, was regarded as the earliest fossil record of non-spicular demosponges. Here we describe the first vauxiid sponge, Vauxia leioia new species, from the early Cambrian Chengjiang Biota (Series 2, Stage 3). This sponge exhibits a double-layered fibrous skeleton: the mesh and fiber thickness of the endosomal layer are irregular while the dermal layer, which directly connects with the endosomal skeleton without intermediate supporting fibers, is regular in both aspects. Measurements using scanning electron microscope and Raman spectroscopy revealed that the endosomal fibers are composed of carbonaceous material, but are tomographically indiscernible from the host rock, while the dermal fibers are preserved as impressions without obvious accumulation of carbonaceous material. Although the original composition of the dermal skeleton is now hard to establish, we cannot rule out that it was siliceous. The morphological characters of V . leioia n. sp. represent an intermediate state between other Vauxia species and the recently established vauxiid genus Angulosuspongia . However, more data are required to reconstruct the phylogenetic relationship among these taxa. UUID: http://zoobank.org/0ebb91b8-5dad-420f-bb2c-dc203d37bebd